Avaliação da influência da carbodiimida na reciclagem de tecidos a base de PA6 - Baccarin, Graziela Solferini (2023)
The remaining fabric from the textile industry, especially that related to clothing, is a growing environmental and economic problem. On a global scale, in 2015, 92 million tons of fabric were discarded and it is expected that by 2030 this number will increase to 148 million tons. Concomitantly with consumption, there is disposal that occurs in landfills, through incineration for conversion into energy, and also inappropriately in landfills. An alternative to disposing of waste from the textile industry is its recycling. Therefore, in this project, post-industrial waste polyamide 6 (PA6) was recycled with the aim of developing a material that can return to its original application, promoting adequate circularity. Furthermore, the influence of the presence of carbodiimide, as a functional molecule, on the recycling of dry and wet PA6 was studied. The results of X-ray diffraction and differential scanning calorimetry indicated that there was a change in the crystalline phase of PA6 from α to γ with the incorporation of CDI. The rheology results indicated an increase in molar mass of 73% for dry samples and 147% for wet samples, indicating that carbodiimide is more effective in humid media. Intrinsic viscosity analyzes together with rheology analyzes indicated that the increase in CDI probably induces the formation of long branches. Finally, the mechanical tests indicated that for the dry samples there was an increase in tensile strength, while for the wet samples there was no change. These tests also indicated that carbodiimide increases the ductility of PA6, with dry samples showing an increase of around 70% in elongation at break, while wet samples showed an increase of around 55%.